Investigation of borided layers contribution on the wear resistance and adhesion of TiN coatings - Almeida,Elisangela Aparecida dos Santos de (2017)
ABSTRACT The purpose of the investigation was to examine the possibility of improving tool life by reducing the wear effect and improving the adhesion of a thin film through a compound configuration that consists in boriding and PVD deposition. Single layer coatings of TiN were deposited by PVD (cathodic arc) on quenched and tempered and on borided powder metallurgy (P/M) AISI M2 steel. Adhesion test was performed according VDI 3198. Microhardness measurements were performed on Vickers scale and the tribological behavior evaluated through dry sliding wear test, using a ball-on-disk apparatus. The wear tracks were analyzed through scanning electron microscopy (SEM) and confocal microscopy. After the wear test the samples were transversally cut, coating and substrate were investigated using scanning electron microscopy (SEM). The results showed a better adhesion of the coating for the borided sample comparing to the quenched and tempered sample. The wear mechanisms of quenched/tempered-TiN (Q/T-TiN) samples against Al2O3 ball were different from the wear mechanisms of borided-TiN (B-TiN) sample against Al2O3 ball.